Fractionation of Allium giganteum Effective Extract on Gastrointestinal Neoplasms Cell Lines for Its Anti-Proliferative Properties - Sadeghi Dinani, Masoud; Ghanbarzadeh, Mohammadreza; Shafiee, Fatemeh (Advanced biomedical research, 2025)
Background: This study was designed to investigate the various extracts of Allium giganteum in term of their cytotoxic effects on gastric and colon cancer cell lines and then fractionation of extract with the most desired effects on cancer cells in comparison to the normal cell line. Materials and Methods: The A. giganteum air-dried bulbs were extracted in four solvents including aqueous, butanol, chloroform: methanol (9:1), and dichloromethan extracts. Evaluating the cytotoxicity of extracts were done by MTT assay against HT-29, KATO-III, and HUVEC cell lines. The extract with The most cytotoxicity on cancer cells and lower toxicity on normal cell line was subjected to the fractionation by MPLC using a RP-18 silica gel column and in the next stage and the cytotoxicity of resulted fractions were determined by MTT assay. Results: Chloroform: methanol extract was the safest extract on HUVEC cells with great cytotoxic effects against cancer cell lines (IC50 17.3 and 23 µg/mL, for KATO-III and HT-29, respectively). The results of MTT assay for 7 fractions of the chloroform: methanol extract showed that 5th fraction (E) was the most cytotoxic fraction (IC50 9 and 11.2 µg/mL for HT-29 and KATO-III, respectively). TLC and NMR analysis of the fractions suggested the presence of steroidal saponins as the main constituents. Conclusion: Significant cytotoxic effects of Allium giganteum was established against GI cancer cell lines especially fractions rich in steroidal saponins. So, these fractions are attractive candidate for the isolation and identification of effective ingredients.